Evaluating Price and Availability of Essential Medicines in China: A Mixed Cross-Sectional and Longitudinal Study - Yang, Caijun; Hu, Shuchen; Ye, Dan; Jiang, Minghuan; Babar, Zaheer-Ud-Din; Fang, Yu (Frontiers in Pharmacology, 2020)
Objectives To evaluate the price and availability of medicines in China. Methods A standard methodology developed by WHO and Health Action International (HAI) was used to collect medicine price and availability data. We obtained cross-sectional data for 48 medicines from 519 facilities (280 public hospitals and 239 private retail pharmacies) in five provinces in China in 2018. We also collected longitudinal data for 31 medicines in Shaanxi province in 2010, 2012, 2014 and 2018. Medicine price was compared with international reference price to obtain a median price ratio (MPR). The availability and price in five provinces were compared in matched sets. We used general estimating equations to calculate differences in availability and median prices from 2010 to 2018. Findings Mean availability of surveyed medicines in five provinces was low in both public (4.29%- 32.87%) and private sectors (13.50%-43.75%). The MPR for lowest priced generics (LPGs) were acceptable (1.80-3.02), for originator brands (OBs) were much higher (9.14-12.65). The variation was significant for both availability and price of medicines across provinces. In Shaanxi province, the availability of medicines decreased between 2010 and 2018, but this was not significant in public or private sector. Compared with 2010, the median adjusted patient price was significantly lower in 2018 for 9 OBs (difference -22.4%; p=0·005) and 20 LPGs (-20.5%; p=0·046) in the public sector, and 10 OBs (-10.2%; p=0.047) in the private sector. Conclusion Access to medicines was found to be poor and unequal across China in 2018. Future interventions are needed, and possible strategies include effective and efficient procurement, promoting development of retail pharmacies and increasing medicine price transparency.